System of Nation Accounting in Nepal - Gewali, Babu Ram (Economic Journal of Nepal, 2005)
National accounting or social accounting is an important concept in an economy. It is, on one side, a tool for the analysis of the trend of the economy and on the other side it is a goal also. Every economy tries to increase and redistribute the national income. The regular and scientific estimation of national income (NI) was started in Nepal since 1974. The process of the calculation of GDP is quite a long and complicated process. A brief discussion of the process of GDP estimation along with NI statistics of Nepal from the beginning is given in this paper. Economic Journal of Nepal Vol.28(3) 2005 pp.178-187